2021
DOI: 10.1177/02841851211022501
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis of early pneumoconiosis in dust-exposed workers: comparison of chest radiography and computed tomography

Abstract: Background Chest radiography (CR) is employed as the evaluation of pneumoconiosis; however, we sometimes encounter cases in which computed tomography (CT) is more effective in detecting subtle pathological changes or cases in which CR yields false-positive results. Purpose To compare CR to CT in the diagnosis of early-stage pneumoconiosis. Material and Methods CR and CT were performed for 132 workers with an occupational history of mining. We excluded 23 cases of arc-welder’s lung. Five readers who were experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In terms of pneumoconiosis, the thoracic CT images have the potential to provide an essential feature for distinguishing subtle morphological patterns of micro-nodule distributions. 7,8 Recent progress of quantitative computed tomography (QCT)-based analysis has spawned research on object assessment of alterations secondary to pneumoconiosis. [9][10][11][12][13][14] The QCT-based image analysis allows for accurate evaluation and monitoring of pneumoconiosis.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of pneumoconiosis, the thoracic CT images have the potential to provide an essential feature for distinguishing subtle morphological patterns of micro-nodule distributions. 7,8 Recent progress of quantitative computed tomography (QCT)-based analysis has spawned research on object assessment of alterations secondary to pneumoconiosis. [9][10][11][12][13][14] The QCT-based image analysis allows for accurate evaluation and monitoring of pneumoconiosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, majority of the conventional methods are based on the subjective assessment of radiologists, that is, failure of accurately identifying small opacities or oversight on assessing the degree of disease progression (J-P et al, 2023). Recently, several studies have demonstrated that CT provides better sensitive results, compared with chest X-rays, implying that CT is considered as an effective method for diagnosing pneumoconiosis (Takahashi et al, 2018;Hayashi et al, 2022). In addition, quantitative computed tomography (QCT)-based analysis is gaining widespread attention as an effective tool that can more accurately and objectively assess alterations secondary to pneumoconiosis (Liu et al, 2002;Xia et al, 2012).…”
Section: Introductionmentioning
confidence: 99%